The Impact of COVID-19 on Small Business Owners: The First Three Months after Social-Distancing Restrictions - Robert W. Fairlie (Institute of Labor Economics (IZA), 2020)
Social distancing restrictions and health- and economic-driven demand shifts from COVID-19 are expected to shutter many small businesses and entrepreneurial ventures, but there is very little early evidence on impacts. This paper provides the first analysis of impacts of the pandemic on the number of active small businesses in the United States using nationally representative data from the April 2020 CPS – the first month fully capturing early effects. The number of active business owners in the United States plummeted by 3.3 million or 22 percent over the crucial two-month window from February to April 2020. The drop in active business owners was the largest on record, and losses to business activity were felt across nearly all industries. African-American businesses were hit especially hard experiencing a 41 percent drop in business activity. Latinx business owner activity fell by 32 percent, and Asian business owner activity dropped by 26 percent. Simulations indicate that industry compositions partly placed these groups at a higher risk of business activity losses. Immigrant business owners experienced substantial losses in business activity of 36 percent. Female business owners were also disproportionately affected (25 percent drop in business activity). Continuing the analysis in May and June, the number of active business owners remained low – down by 15 percent and 8 percent, respectively. The continued losses in May and June, and partial rebounds from April were felt across all demographic groups and most industries. These findings of early-stage losses to small business activity have important implications for policy, income losses, and future economic inequality.
Keywords: J15; J16; L26; 330; small business; entrepreneurship; business owners; self-employment; COVID-19; coronavirus; shelter in place restrictions; social distancing restrictions; minority business; female